Women’s Perception of Transgastric and Transvaginal Natural Orifice Transluminal Endoscopic Surgery (NOTES) – Impact of Medical Education, Stage of Life and Cross-Cultural Aspects - Benhidjeb T; Benhidjeb I; Stark M; Kreisel S; Krüger M; Pfitzenmaier J; Schulte am Esch J (Dove Medical Press, 2022)
Tahar Benhidjeb,1,2,* Isabel Benhidjeb,3,* Michael Stark,2 Stefan Kreisel,4 Martin Krüger,5 Jesco Pfitzenmaier,3,* Jan Schulte am Esch1,* 1Department of General and Visceral Surgery, Center for General, Vascular, Thoracic and Visceral Surgery, Protestant Hospital of Bethel Foundation, University Hospital OWL, Campus Bielefeld Bethel, University of Bielefeld, Bielefeld, Germany; 2The New European Surgical Academy (NESA), Berlin, Germany; 3Department of Urology, Center for Computer-Assisted and Robotic Urology, Protestant Hospital of Bethel Foundation, University Hospital OWL, Campus Bielefeld Bethel, University of Bielefeld, Bielefeld, Germany; 4Department of Psychiatry and Psychotherapy, Section Gerontopsychiatry, Protestant Hospital of Bethel Foundation, University Hospital OWL, Campus Bielefeld Bethel, University of Bielefeld, Bielefeld, Germany; 5Department of Internal Medicine and Gastroenterology, Protestant Hospital of Bethel Foundation, University Hospital OWL, Campus Bielefeld Bethel, University of Bielefeld, Bielefeld, Germany*These authors contributed equally to this workCorrespondence: Tahar Benhidjeb, Department of General and Visceral Surgery, Center for General, Vascular, Thoracic and Visceral Surgery, Protestant Hospital of Bethel Foundation, University Hospital OWL, Campus Bielefeld Bethel, University of Bielefeld, Schildescher Str. 99, Bielefeld, 33611, Germany, Email tahar.benhidjeb@yahoo.de; tahar.benhidjeb@evkb.deIntroduction: Despite that NOTES produces at least matchable clinical long-term results when compared to laparoscopy, still a restraint within the medical community and among patients is evident. Consequently, it might be meaningful to evaluate factors of patient's NOTES perception to promote its acceptance. NOTES is still quite novel and questionnaires regarding its perception by the public is still lacking even so in the Middle East. Aim of our survey is to investigate the viewpoint of female healthcare staff on NOTES.Materials and Methods: A total of 350 questionnaires along with written information about Minimally Invasive Surgery and NOTES were distributed among the female staff in a Tertiary-care Hospital in Abu Dhabi, 257 were returned completely anonymously and voluntarily and entered into a database with a response rate of 73%. We surveyed factors like religion, medical background, age as well as history of previous laparoscopy, endoscopy, birth and other aspects that may impact a woman's perception of both transgastric and transvaginal NOTES for cholecystectomy and ovariectomy, respectively.Results: Univariate analyses revealed the majority of Muslim women to be more receptive to NOTES as a choice of surgical technique for cholecystectomy and for ovariectomy, respectively, when compared to Christians and Hindus. However, when compared to Muslims, Christian and Hindu groups had a larger share of medical professions. Women with a medical background would opt significantly less for NOTES. Among younger women, NOTES cholecystectomy was refused due to anxiety concerning future pregnancies and sexual dysfunction. Multinomial logistic regression analysis determined medical background and with independent predictive value for the overall choice of interventional technique (p< 0.001). Marital status played a significant role only in the comparison of laparoscopy vs transgastric NOTES when performing cholecystectomy and ovariectomy (p< 0.01).Conclusion: In this first study emanating from the Middle East, medical education and partly life stage rather than cross-cultural differences seem to influence NOTES perception in women.Keywords: natural orifice translumenal endoscopic surgery, perception, Arab female